2018
DOI: 10.1177/0306624x18818922
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Cycle: Understanding the Needs of Women Involved in the Criminal Justice System and the Role of Mentoring in Promoting Desistance

Abstract: An increasingly popular gender-specific intervention to assist women involved in the criminal justice system (e.g., ex-prisoners) is mentoring. However, despite the growing popularity of mentoring, there is a dearth of literature that has explored the intervention’s efficacy, particularly as it relates to women involved in the criminal justice system. In the current study, client files of 64 women in a one-to-one mentoring program in Australia were examined to identify (a) the social and practical needs and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Mentoring involves interaction between two individuals, over time, whereby a mentee is in a position to imitate or benefit from a mentor with greater experience, knowledge, or power (Tolan et al, 2008). Though popular, there is little evidence of the intervention’s efficacy in terms of recidivism reduction (Singh et al, 2019; Wincup, 2019) and it is often found to be a “promising not proven intervention” (Jolliffe and Farrington, 2008: 9). There are, however, other benefits to mentoring.…”
Section: Practical Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentoring involves interaction between two individuals, over time, whereby a mentee is in a position to imitate or benefit from a mentor with greater experience, knowledge, or power (Tolan et al, 2008). Though popular, there is little evidence of the intervention’s efficacy in terms of recidivism reduction (Singh et al, 2019; Wincup, 2019) and it is often found to be a “promising not proven intervention” (Jolliffe and Farrington, 2008: 9). There are, however, other benefits to mentoring.…”
Section: Practical Mattersmentioning
confidence: 99%
“…There are, however, other benefits to mentoring. In sum, a mentor can aid in the development of bridging social capital by providing the mentee with relational support, practical assistance, and access to more diverse social networks (Brown and Ross, 2010; McNeill et al, 2012; Singh et al, 2019; Wincup, 2019). The effectiveness of mentoring programs can be enhanced by ensuring a good match between the mentor and mentee based on common interests and mentor skills (Geither, 2012).…”
Section: Practical Mattersmentioning
confidence: 99%
“…Mentees would often update mentors on their social development, the friends they had made and their own professional networks. Singh, Cale and Armstrong (2018) discuss mentoring as a means of promoting desistance and state: ‘mentoring has been applied in the criminal justice context, typically as a tertiary intervention strategy to address relational deficits in the lives of offenders to reduce the likelihood of reoffending’ (p.4). Reintegration and rehabilitation are supported through the mentoring process; mentors accompany ex‐offenders in taking small steps towards their journey to desistance.…”
Section: Mentee‐focused Factorsmentioning
confidence: 99%
“…The impact of arts-based therapeutic programmes on prisoners and those on probation is documented, yet our understanding of mentoring is underdeveloped (see Bozeman and Feeney 2007;Buck 2018;Singh, Cale and Armstrong 2018) We felt it appropriate to explore the other half of the mentor-mentee relationship, specifically studying the experiences of artists who volunteer to mentor ex-offenders from an arts-based 484 C 2020 The Authors. The Howard Journal of Crime and Justice published by Howard League and John Wiley & Sons Ltd This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.…”
mentioning
confidence: 99%
See 1 more Smart Citation